2006
DOI: 10.1038/sj.jp.7211524
|View full text |Cite
|
Sign up to set email alerts
|

Neonatology fellowship training in research pertaining to development and follow-up

Abstract: The methodology of the study of the short-and long-term outcomes has changed over the 30-40 years since the indroduction of neonatal intensive care. The training of neonatal fellows in research pertaining to development and follow-up currently needs to include study of epidemiology and biostatistics, knowledge concerning normal and abnormal growth and development throughout the life span and clinical skills and/or knowledge concerning the assessment of neurologic and developmental outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Gestational age has a more linear relationship with ICI prevalence compared with birth weight, and aids in defining the highest-risk patients [20,[22][23][24]. For example, growth charts demonstrate that a 24-week gestation infant could weigh between 468 and 940 g (3rd to 97th percentiles) [25].…”
Section: What Is the Incidence Of Ici In Your Nicu?mentioning
confidence: 99%
“…Gestational age has a more linear relationship with ICI prevalence compared with birth weight, and aids in defining the highest-risk patients [20,[22][23][24]. For example, growth charts demonstrate that a 24-week gestation infant could weigh between 468 and 940 g (3rd to 97th percentiles) [25].…”
Section: What Is the Incidence Of Ici In Your Nicu?mentioning
confidence: 99%
“…Weitkamp et al recently reported the importance of examining ICI incidence in each NICU, as many flaws exist when relying solely on literature for the condition (Weitkamp et al, 2008). This NICU reported that while their rate of Candida BSIs was 6.8%, the rate of all ICI was 10% for infants weighing less than 1000 g. Gestational age has a more linear relationship to ICI compared to birth weight and it aids in defining the highest risk patients (Makhoul et al, 2007;Clerihew et al, 2006;Johnsson and Ewald, 2004;Hack, 2006). For example, growth charts demonstrate that a 24-week gestation infant could be between 468 and 940 g (3rd to 97th percentiles) (Kramer et al, 2001).…”
Section: Ici Variation Among Nicusmentioning
confidence: 99%
“…1,21 Gestational age has a more linear relationship to ICI compared to birth weight and captures the highest-risk patients. [22][23][24] For example, examining growth charts, a 24-week gestation infant could be between 468 to 940 g (3rd to 97th percentiles). 25 As this study demonstrated, by examining the incidence of ICI by each gestational age and birth weight, they were able to see where the rates in their population fell to zero.…”
Section: Prophylaxismentioning
confidence: 99%